2021
DOI: 10.1186/s12889-021-12194-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity related to mastery and vitality in a Swedish adult population with economic difficulties

Abstract: Background People with low socio-economic status report lower levels of physical activity (PA). There is insufficient knowledge about the availability of psychological resources for those who are physically active despite having a low socio-economic status. The aim of this study is to investigate the association between PA level and mastery and vitality, respectively, within an adult population with self-reported economic difficulties. Method Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Vitality is a unidimensional construct that considers both negative and positive states; that is, the presence of energy (energy as a positive asset) and the absence of fatigue (fatigue as a negative indicator/hinderance to vitality) [ 14 ]. Vitality also links integrated biopsychosocial theories of human functioning along a health continuum [ 109 , 110 , 111 , 112 ]. The research shows that vitality is positively associated with an individual’s quantity and quality of social contacts [ 113 ], and while vitality appears to be a factor in the promotion/maintenance of healthy lifestyle behaviors, intervention studies suggest that vitality is also a product of healthy dietary practices and regular physical activity [ 114 , 115 ].…”
Section: The Case For Including Vitality: More Comprehensive Assessme...mentioning
confidence: 99%
“…Vitality is a unidimensional construct that considers both negative and positive states; that is, the presence of energy (energy as a positive asset) and the absence of fatigue (fatigue as a negative indicator/hinderance to vitality) [ 14 ]. Vitality also links integrated biopsychosocial theories of human functioning along a health continuum [ 109 , 110 , 111 , 112 ]. The research shows that vitality is positively associated with an individual’s quantity and quality of social contacts [ 113 ], and while vitality appears to be a factor in the promotion/maintenance of healthy lifestyle behaviors, intervention studies suggest that vitality is also a product of healthy dietary practices and regular physical activity [ 114 , 115 ].…”
Section: The Case For Including Vitality: More Comprehensive Assessme...mentioning
confidence: 99%
“…We believe that such results are quite natural because, as we pointed out in the introduction, the concept of general resistant resources occupies an important place in the salutogenic approach and describe one's capability to successfully cope inherent stress factors of human existence (Johansson et al 2021). In our opinion, this concept is quite closely related to the concept of 'hardiness', which reveals the psychological mechanisms of a person's capability to maintain their health regardless of highly stressful life events (Kobasa 1979;Kobasa et al 1982), which is especially important in the stressful conditions of life at the Antarctic station.…”
Section: Discussionmentioning
confidence: 85%
“…The concept of general resistant resources is another important component of the salutogenic approach. It describes a person's capability to successfully cope with the inherent stressors of human existence (Johansson et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the associations between PA and IC were mainly reflected in three domains: locomotion, cognition, and vitality, and the study in Japan found the significant associations in the same domains but not the cognition [ 15 ]. Supervised physical exercise programs addressed towards older adults have been shown to contribute to an improvement in physical parameters such as cardiorespiratory fitness, gait, muscle strength, and clinical balance outcomes [ 25 , 26 , 27 ], which in turn delays several geriatric syndromes and improves locomotion [ 28 ] and vitality [ 29 , 30 ]. Besides these two domains of IC, PA was also identified as a potent lifestyle factor critical in reducing cognitive decline and improving cognitive function in older adults with different study designs [ 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%